Isolation, characterization and overexpression of Chalcone synthase gene in suspension cultures of Boesenbergia rotunda / Nurnadiah Roslan - Nurnadiah , Roslan (2017)
Boesenbergia rotunda (L.) Mansf. is a herb plant from Boesenbergia genera and belongs to Zingiberaceae family. In some Asian countries, it is commonly consumed as a traditional meal or used as a spice ingredient and traditional medicine. Its ethnomedicinal properties derived from rhizome extracts have broadly drawn attention to further explore its medicinal and health values. The bioactive compounds from rhizome extracts are plant secondary metabolites synthesized from the flavonoid biosynthesis pathway by a number of enzymes. In most of the plants, chalcone synthase (CHS) is the first key enzyme that initiates the biosynthesis of flavonoid. In this study, at least four to five copies of BrCHS were successfully detected and predominantly expressed in a tissue-specific manner. BrCHS2 isolated from the rhizomes was chosen to be introduced into B. rotunda suspension culture to observe the potential effects of different BrCHS levels on flavonoid accumulation and regulation of gene expression in the plant pathways. The transcript variant from rhizome was chosen because it is the most relevant variant with medicinal interest as it has been utilized to be expressed and produced compound that serve pharmaceutical benefits. The enzymatic properties of the BrCHS2 showed that it has utilized Cinnamoyl-CoA as substrate to produce compound for pinocembrin chalcone. The reaction was accompanied by the formation of unidentified products. Focus on elucidating potential genes related to flavonoid biosynthesis was further carried out using high-throughput RNA sequencing (RNA-Seq). The mass of transcript sequences obtained from RNA-Seq led to the annotation of functional genes affected by the influence of increasing the expression BrCHS. In order to determine and annotate their functions, a total of 67,251 (65.8%) unigenes were successfully cross referenced to several public databases. An inter-sectioned between three groups of wild-type (WT) and transgenic (TL) produced 3,148 differentially expressed genes, of which 1,905 were up-regulated and 1,043 were down-regulated in the suspension culture library. Looking at the distribution of differentially expressed genes, the overall picture showed that there were relatively higher numbers of upregulated genes in the transgenic suspension cultures compared to wild-type as the result of BrCHS overexpression. However, further comparative analysis against the KEGG database highlighted the fact that for flavonoid biosynthesis and related pathways, there were actually more down-regulated genes. Due to the overexpression of BrCHS, unigenes that were responsible for plant defense pathway have also increased as a response towards stress, and thus obtained important function on plant resistance. With sufficient data and transcripts obtained, the potential unigenes that could be applied to synthesize targeted compounds, especially in the flavonoid biosynthesis pathway responsible for the potent medicinal properties production, could be identified for ultimate use in future drug analysis.